Early Hospital Readmission After Laparoscopic Cholecystectomy. Issue 3 (June 2015) - Simsek, Gurcan; Kartal, Adil; Sevinc, Baris; Tasci, Halil I.; Dogan, Serhat
<x xml:space="preserve">Abstract</x> Introduction: Laparoscopic cholecystectomy (LC) now has become the golden standard in the treatment of symptomatic gallstone cholecystitis. Aim: This retrospective analysis was conducted to clarify the reasons of early return to the hospital after discharge following a procedure like LC that has been frequently performed in daily surgical practice. Materials and Methods: This study covers 586 patients, who were called to follow-ups and thus evaluated, of 676 patients who had had LCs at Meram Medical School's General Surgery Clinic between January 2010 and May 2011. Findings: The rate of representation to the hospital during the early phase following LC was found to be 2.4% in our study. It was observed that 71% of returning patients had presented to the hospital with complaints of abdominal pain. Discussion: We believe that the rate of 2.4% early return to the hospital in our series is a bit high when all the complications are taken into consideration. This retrospective analysis, however, has shown that this rate can further be decreased by taking simple measures.